Modifications of the GH Axis Reveal Unique Sexually Dimorphic Liver Signatures for Lcn13 , Asns , Hamp2 , Hao2 , and Pgc1a - Brie, Belen (2024)
Growth hormone (GH) modifies liver gene transcription in a sexually dimorphic manner to meet liver metabolic demands related to sex; thus, GH dysregulation leads to sex-biased hepatic disease. We dissected the steps of the GH regulatory cascade modifying GH-dependent genes involved in metabolism, focusing on the male-predominant genes Lcn13, Asns, and Cyp7b1, and the female-predominant genes Hao2, Pgc1a, Hamp2, Cyp2a4, and Cyp2b9. We explored mRNA expression in 2 settings: (i) intact liver GH receptor (GHR) but altered GH and insulin-like growth factor 1 (IGF1) levels (NeuroDrd2KO, HiGH, aHepIGF1kd, and STAT5bCA mouse lines); and (ii) liver loss of GHR, with or without STAT5b reconstitution (aHepGHRkd, and aHepGHRkd + STAT5bCA). Lcn13 was downregulated in males in most models, while Asns and Cyp7b1 were decreased in males by low GH levels or action, or constant GH levels, but unexpectedly upregulated in both sexes by the loss of liver Igf1 or constitutive Stat5b expression. Hao, Cyp2a4, and Cyp2b9 were generally decreased in female mice with low GH levels or action (NeuroDrd2KO and/or aHepGHRkd mice) and increased in HiGH females, while in contrast, Pgc1a was increased in female NeuroDrd2KO but decreased in STAT5bCA and aHepIGF1kd females. Bioinformatic analysis of RNAseq from aHepGHRkd livers stressed the greater impact of GHR loss on wide gene expression in males and highlighted that GH modifies almost completely different gene signatures in each sex. Concordantly, we show that altering different steps of the GH cascade in the liver modified liver expression of Lcn13, Asns, Cyp7b1, Hao2, Hamp2, Pgc1a, Cyp2a4, and Cyp2b9 in a sex- and gene-specific manner.